Thermal balneotherapy in Antsirabe-Madagascar: water analysis and its applications in an African context - Pedrazzini, Alessio; Delsignore, Roberto; Martelli, Alessandra; Tocco, Silvio; Vaienti, Enrico; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2016)
The Orthopaedic Rehabilitation Centre of Madagascar can be found in the city of Antsirabe. The health care facility is equipped with 2 thermal sources of bicarbonate water used for post-operative rehabilitation and for the ailment of chronic degenerative illnesses. The aim of this study, which derives from the cooperation between the School of Specialization in Thermal Therapy of the University of Parma and Antsirabe Orthopaedic Hospital, is to analyze the real properties of thermal waters utilized in this centre and to do an overview of its possible applications in this particular African context.